A Research Study to Increase Usage of PVs in Residential Areas - Kiray, Vedat (Frontiers in Energy Research, 2021)
Self-generation of energy by residential houses has been met with many obstacles. When PV Solar energy technology is considered, the barriers manifest in problems related to the location, slope, strength, and shade exposure of house roofs are the most common. Therefore, it is not possible to meet daily energy needs from PV panels placed on the existing roofs of many houses. Solar Tracking Systems keep PV panels perpendicular to the Sun throughout the day, providing a significant increase in their efficiency. But the application of these systems on the roofs or houses is not suitable for many reasons, especially in terms of aesthetic appearance. This article is aimed at effectively showing how the slope and direction inconsistencies in the existing roofs of houses in residential areas cause great losses in the performance of PVs; also a research and design study is presented to find a solution to the application of Sun tracking systems in residential areas without creating aesthetic appearance problem. As a solution, combining a dual axis Sun tracking system with an aesthetic looking Gazebo has been considered. A design study was carried out for the targeted system, and the dimensions of a movable platform/roof such a system should have in order to meet the electricity needs of a house from the Sun throughout the year was investigated. How much energy the PV panels can collect annually is determined by a simulation program called “PV performance tool”.